Hope and Deception in Conception Bay: Merchant-Settler Relations in Newfoundland 1785-1855 - Bumsted, J. M. (Labour / Le Travail, 1996)
The article reviews the book "Hope and Deception in Conception Bay: Merchant-Settler Relations in Newfoundland 1785-1855," by Sean T. Cadigan.
Keywords: BOOKS – Reviews; BUSINESSPEOPLE; CADIGAN; Sean T.; HOPE & Deception in Conception Bay: Merchant-Settler Relations in Newfoundland 1785-1855 (Book); Nonfiction